SÃ”BRE O PERÃODO DE GESTAÇÃO NAS RAÇAS ZEBUINAS: I- RAÇA GUZERAT - Briquet Junior, Raul; Abreu, Jorge de (REVISTA DE AGRICULTURA, 2016)
SÃ”BRE O PERÃODO DE GESTAÇÃO NAS RAÇAS ZEBUINAS: I- RAÇA GUZERAT